End-of-Life care: advanced care planning, euthanasia and suicide - Rosenfeld, Lilia (Humaniora. Czasopismo Internetowe, 2019)
End-of-life planning for elderly people provides a necessary condition for a respectable and decent aging and death, which meets the wishes and expectations of the elderly person. Nevertheless, decision-making in this respect is based on the values and experience of formal and informal caregivers that are often ignorant of the wishes of the elderly. Respectively, the elderly person’s wish to end life should be viewed as a call for help and distress, as the phenomenon becomes more frequent. Elderly people do not really wish to die. Rather, they fear end-of-life treatments that are performed against their wish and beyond their control in a humiliating and painful manner, and without truly offering benefit to their lives. Consequently, elderly people see death as a relief from pain and a promise for peace. Moreover, choosing death over life, provides the elderly person with a renewed sense of control. Thus, the Western society pushes the elderly person to prefer euthanasia or suicide over a life of dependence, humiliation and pain.